2012
DOI: 10.1007/s11743-012-1370-z
|View full text |Cite
|
Sign up to set email alerts
|

2‐[(E)‐{(1S,2R)‐1‐Hydroxy‐1‐phenylpropan‐2‐ylimino}methyl]phenol for Inhibition of Acid Corrosion of Mild Steel

Abstract: 2‐[(E)‐{(1S,2R)‐1‐hydroxy‐1‐phenylpropan‐2‐ylimino}methyl]phenol has been synthesized and its influence on corrosion of mild steel in 1 M HCl solution has been studied by means of weight loss and electrochemical measurements under various circumstances. The inhibitor showed a maximum of 91 % of inhibition efficiency at 100 ppm. Interestingly, the inhibition efficiency has decreased on increasing the inhibitor concentration. This abnormal behavior is attributed to the release of phenolic hydrogen from the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, the anionic surfactant/ethanol mixed system was also found to adsorb onto carbon steel under acid conditions as confirmed using scanning electron microscopy (SEM), X‐ray diffraction (XRD), and energy‐dispersive X‐ray (EDX) (El‐Tabei and Hegazy, ). The 2‐[( E )‐{(1 S ,2 R )‐1‐hydroxy‐1‐phenylpropan‐2‐ylimino}methyl]phenol substance was also found to adsorb onto the steel surface as confirmed using ultra violet–Visible spectroscopy where the chemical interaction of the substance and the metal surface was detected (Kesavan et al, ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the anionic surfactant/ethanol mixed system was also found to adsorb onto carbon steel under acid conditions as confirmed using scanning electron microscopy (SEM), X‐ray diffraction (XRD), and energy‐dispersive X‐ray (EDX) (El‐Tabei and Hegazy, ). The 2‐[( E )‐{(1 S ,2 R )‐1‐hydroxy‐1‐phenylpropan‐2‐ylimino}methyl]phenol substance was also found to adsorb onto the steel surface as confirmed using ultra violet–Visible spectroscopy where the chemical interaction of the substance and the metal surface was detected (Kesavan et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…The surfactant-metal surface interaction during the adsorption process is one of the most important factors behind the inhibition effect of these materials. Adsorption of ionic and nonionic surfactants onto metal surfaces was confirmed by many authors (Deyab, 2015;El-Tabei and Hegazy, 2013;Kesavan et al, 2012). In acidic solutions, it was found that nonionic surfactants physically adsorb onto the carbon steel surface obeying the Langmuir adsorption isotherm (Deyab, 2015).…”
Section: Corrosion Of Zn Powder In C N Tab/hcl Solution (Conductivitymentioning
confidence: 84%
“…Linear relationship was observed for the data only in the case of Langmuir adsorption isotherm (Fig.2). The Langmuir adsorption isotherm can be understood from the relationship between surface coverage and the inhibitor concentration as shown in the following equation (4).…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Inhibitors from natural resources such as plants are interesting since they are abundant, economical, and environmentally friendly. In order to explore the efficient organic inhibitors, the authors have studied several synthetic as well as plant-based green inhibitors against the corrosion of steels in different media [3][4][5][6] . In an effort to contribute to the current interest on development of the ecofriendly inhibitors, in this study, the authors examined the ethanolic leaf extract of Jacaranda mimosifolia (JM) against the corrosion of steel in 1.0 M HCl.…”
Section: Introductionmentioning
confidence: 99%
“…Cast iron specimens containing 6.09 % C, 1.13 % Al, 0.78 % Mn, with the remainder being Fe, were used for mass loss measurements, which were performed according to previous reports of one of the authors [8,[14][15][16]. In brief, rectangular cast iron coupons 2 9 1.5 9 0.02 cm in size were abraded using 600, 800, 1,000, and 1,200 grit emery papers, and then washed thoroughly with double distilled water, degreased with acetone and dried at room temperature and then weighed.…”
Section: Mass Loss Measurementsmentioning
confidence: 99%